Model Inovasi Pembelajaran Bahasa Arab di PKPBA UIN Maulana Malik Ibrahim Malang - A. Samsul Ma'arif; Nasikhin Muad; Nur Arifuddin; Ali Maksum (Fakultas Tarbiyah Institut Pesantren Sunan Drajat Lamongan, 2026)
This study aims to analyze the forms of Arabic language learning innovation implemented at the Center for Arabic Language Development (PKPBA) of UIN Maulana Malik Ibrahim Malang and to identify factors supporting their successful implementation. The research employed a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews with program administrators and instructors, and documentation analysis. The findings show that PKPBA implements integrated learning innovations through: (1) communicative skill-based curriculum development, (2) immersion learning supported by a total Arabic environment, (3) the utilization of digital media and Learning Management Systems (LMS), (4) authentic assessment through portfolio and oral examinations, and (5) continuous professional development for instructors and peer tutors. These innovations contribute to improving students’ motivation, confidence, and communicative competence, reflected in the high competency examination achievement rate. The study concludes that institutional commitment, lecturer professionalism, and a supportive language environment are the main factors contributing to the effectiveness of learning innovation at PKPBA. This study recommends the development of adaptive technology-based learning and the wider adoption of integrated innovation models in Arabic language education institutions